PERENCANAAN PENGEMBANGAN SISTEM PEMBANGKIT LISTRIK DI PULAU JAWA - Aas Wasri Hasanah; Andi Makkulau; Zulfahmi Faisal Fadhilah (Sekolah Tinggi Teknik - PLN, 2015)
Electrical power system is an electrical system consisting of generating systems, distribution systems, and power user installation systems. Generating system functions to generate electricity, the distribution system serves to distribute electric power generated from the generating system to the power user installation system, and the power user system serves to supply electrical equipment in order to operate. The demand for electricity increases every one to keep up with population growth and overall economic growth. One important factor to support the development is the electric power that must be fulfilled by the power supply company, in this case is PT. PLN (Persero). The demand for electricity in Java is the largest in Indonesia, because the population of Java Island is predominantly Indonesian, and Java is the center of all economic activities including industry, commerce / business, government and tourism. For that required additional power generation in the future with the planning of power generation system development in Java for the year 2015 - 2024.